Lies women believe and the truth that sets them free - Wolgemuth, Nancy DeMoss (Chicago : Moody Press, 2001)
We are like Eve. We have all experienced defeats and failures, trouble and turmoil. We have all experienced a selfish heart, a shrewish spirit, anger, envy and bitterness. And we ache to do things over, to have lives of harmony and peace. In her book, Lies Women Believe, author Nancy Leigh DeMoss exposes those areas of deception most commonly believed by Christian women: Lies about themselves: I should not have to live with unfulfilled longings. Lies about sin: I cannot walk in consistent victory over sin. Lies about their marriage: If I submit to my husband, I will be miserable. Lies about their emotions: I can't control my emotions. Lies about their circumstances: I just can't take any more. Nancy Leigh DeMoss sheds light on how we can be delivered from bondage and set free to walk in God's grace, forgiveness, and abundant life. This book offers the most effective weapon to counter and overcome Satan's deceptions -- God's truth. - Publisher
Are you burned out, overwhelmed, angry, confused or fearful? According to Nancy Leigh DeMoss, these emotions are the result of Satan's lies. Nancy tackles many of the falsehoods that enslave Christian women with alarming frequency and severity
Introduction -- Section one : Foundations. Prologue -- Truth or consequences -- Section two : Lies women believe. About God -- About themselves -- About sin -- About priorities -- About marriage -- About children -- About emotions -- About circumstances -- Section three : Walking in the truth. Countering lies with the truth -- The truth that sets us free -- Epilogue -- For further help
Includes bibliographical references (pages 281-283)
Keywords: Christian women -- Religious life; Truthfulness and falsehood -- Religious aspects -- Christianity